Assessment of undiagonised anxiety and depression in patients attending teritiary care teaching hospital and role of clinical pharmacist in management - Viriti, Uma Sankar; B, Kavya Sri; C, Aruna Kumari; P, Sindhuja; P, Sowmya (International Journal of Current Innovations in Advanced Research, 2025)
Background:This research focuses on observing the mental health conditions of patients who are suffering from undiagnosed anxiety and depression attending tertiary care teaching hospital. We have evaluated and observed the number of participants of the study are being suffered and assessed the role of clinical pharmacist in identification and management.Methodology: The present study is a prospective observational analytical study involving 135 study participants who are having anxiety & depression but are being undiagnosed at tertiary care hospital Anil Neerukonda Hospital in Vizianagaram district. The Information was obtained through direct interaction with patients from different departments and they’re diagnosed using State Trait Anxiety Scale (STAI) and Beck Depression Inventory Scale (BD-II).Results:In the study, we reported a prevalence of 51% suffering from anxiety, 32% are suffering from depression and 17% are suffering from both anxiety and depression. Among these 13% of the study participants are of Low/No Depression, 6% with Moderate depression and 2% with Severe Depression. Whereas participants with anxiety were reported as 9% suffering with Low/No Anxiety, 12% with Moderate Anxiety and 0.7% suffering from High Anxiety Levels.Conclusion: Patients who are suffering from undiagnosed anxiety and depression are found to be experiencing trauma, stress and other psychological issues which affects their mental health condition.